UMP acknowledged the sacrifices of its security personnel - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP)’s Registrar Department distributed 29 biscuit packs to its security personnel who would be working during the Aidilfitri celebration as a mark of appreciation to the sacrifice they had to make during the festive season.